2006
DOI: 10.1152/ajpcell.00027.2006
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction channel activity in short-term cultured human detrusor myocyte cell pairs: gating and unitary conductances

Abstract: . Gap junction channel activity in short-term cultured human detrusor myocyte cell pairs: gating and unitary conductances. Am J Physiol Cell Physiol 291: C1366 -C1376, 2006. First published August 9, 2006 doi:10.1152/ajpcell.00027.2006.-Several independent lines of investigation indicate that intercellular communication through gap junctions modulates bladder physiology and, moreover, that altered junctional communication may contribute to detrusor overactivity. However, as far as we are aware, there are stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Analysis of channel kinetics showed that the 26 pS state had much longer open times (31 Ϯ 14 ms, n ϭ 27 patches) and higher open probability (P o , 0.7 Ϯ 0.03) than the fast-gating state in cell-attached patches (P o , 0.006 Ϯ 0.003; p Ͻ 0.01, Student's t test). The substate opening in inside-out patches had a conductance (26 pS) similar to that of the substate of cell-cell channels (26 pS) (Wang et al, 2006). Twenty-six picosiemen openings reversed at the membrane potential near 0 mV (Fig.…”
Section: Characteristics Of Cx43-dependent Channelsmentioning
confidence: 81%
“…Analysis of channel kinetics showed that the 26 pS state had much longer open times (31 Ϯ 14 ms, n ϭ 27 patches) and higher open probability (P o , 0.7 Ϯ 0.03) than the fast-gating state in cell-attached patches (P o , 0.006 Ϯ 0.003; p Ͻ 0.01, Student's t test). The substate opening in inside-out patches had a conductance (26 pS) similar to that of the substate of cell-cell channels (26 pS) (Wang et al, 2006). Twenty-six picosiemen openings reversed at the membrane potential near 0 mV (Fig.…”
Section: Characteristics Of Cx43-dependent Channelsmentioning
confidence: 81%
“…Cx45 37 and Cx43 40,41 appear to be the most prominent Cxs expressed in human detrusor smooth muscle tissue and cultured cells. 39 Observations in tissue biopsies from patients with neurogenic DO 40 and urgency symptoms 41 clearly demonstrated an increase in the presence of Cx43-derived gap junction channels in detrusor muscle. These clinical data are consistent with experimental observations in a rodent model of partial urethral outlet obstruction, 42 which documented a dramatic increase of Cx43 mRNA levels associated with bladder hypertrophy and overactivity following 6 weeks of obstruction.…”
Section: Intercellular Communicationmentioning
confidence: 97%
“…35 -38 The small size of the junctional plaques observed likely accounts for the difficulty in detecting these structures in the first place. Wang et al 39 used double whole-cell patch clamp recordings together with Northern and Western blot techniques to characterize gap junction channel properties, and to evaluate Cx43 expression in human detrusor cells. The presence of Cx43 mRNA and protein in cultured detrusor myocytes, and also in situ, was demonstrated.…”
Section: Intercellular Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main causes is partial bladder outflow obstruction (PBOO), in which overactivity could result neurogenically and/or myogenically from changes in the detrusor innervation and myocyte excitability. Recently, changes in cell-cell communication have been proposed to be one of the possible mechanisms (3,8), and Cx43 plays an important role in the development of DO (6,25). However, the functional changes of cell connectivity in DO are not well elucidated, and there is considerable controversy between reports on changes in cell-cell contact in DO after PBOO.…”
mentioning
confidence: 99%